1999
DOI: 10.1097/00000542-199911000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Staphylococcus aureus in Diprivan and Intralipid 

Abstract: These results suggest that Diprivan, and possibly Intralipid, represent poor media for the growth of S. aureus and may promote infection through mechanisms other than increased inoculum size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 20 publications
3
16
0
1
Order By: Relevance
“…Propofol formulated in lipid supports microbial growth [1][2][3][4]. Propofol was introduced in the USA in 1989 for the induction and maintenance of anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Propofol formulated in lipid supports microbial growth [1][2][3][4]. Propofol was introduced in the USA in 1989 for the induction and maintenance of anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Only Diprivan contains 0.005% w ⁄ v EDTA. Several studies have shown that propofol supports the growth of microorganisms when inoculated in vitro; however, there so not appear to be studies comparing the antimicrobial activity of 0.005% w ⁄ v EDTA in propofol with that of other commercially available formulations [1][2][3][4]. In this study, we compared microbial growth in commercially available formulations, and found that propofol with EDTA suppressed the growth of MSSA, .............................................................................................................................................................................................................. , 62, pages 575-580 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although propofol lipid emulsion is bactericidal or bacteriostatic for some microorganisms such as Staphylococcus aureus (Crowther et al 1996), it does support the growth of other clinically relevant pathogens such as Escherichia coli or Candida albicans (Graystone et al 1997;Wachowski et al 1999). Propofol lipid solutions containing 0.005% (w/v) disodium edetate may have a reduced potency to support bacterial growth, although no clear effect on the rate of bacterial growth after contamination at room temperature could be demonstrated, and Intralipid itself clearly supports bacterial growth − (Fukada and Ozaki 2007;Langevin et al 1999;Vidovich et al 1999). Prolonged infusion of propofol for sedation may cause hypertriglyceridemia, which is a limitation for the use of propofol for long-term sedation (Lindholm 1992;McKeage and Perry 2003).…”
Section: Introductionmentioning
confidence: 99%